L-citrulline treatment alters the structure of the pulmonary circulation in hypoxic newborn pigs - McClellan, Eric B. (Pediatr Pulmonol, 2020)
BACKGROUND: Dysregulated nitric oxide (NO) signaling contributes to chronic hypoxia (CH)-induced pulmonary hypertension (PH). NO signaling is improved and pulmonary vascular resistance (PVR) is reduced in CH piglets treated with the L-arginine-NO precursor, L-citrulline. We hypothesized that L-citrulline might cause structural changes in the pulmonary circulation that would contribute to the reduction in PVR and that the L-citrulline-induced structural changes would be accompanied by alterations in VEGF signaling. METHODS: We evaluated small pulmonary arterial (PA) wall thickness, lung capillary density, and protein abundances of VEGF, VEGFR2, and phospho (p)-VEGFR2 in PA and peripheral lung samples of piglets raised in the lab in CH (10–12% O(2)) from day of life (DOL) 2 until DOL 11–12 or raised in room air (normoxia) by the vendor and studied on arrival to the lab on DOL 11–12. Some CH piglets were treated with oral L-citrulline (1–1.5 g/kg/d) starting on the third day of hypoxia. RESULTS: PA wall thickness was 32% less and lung capillary formation was nearly doubled in L-citrulline treated than untreated CH piglets. Both of these L-citrulline-induced structural changes in the pulmonary circulation were accompanied by altered amounts of VEGF protein but not by altered amounts of either VEGFR2 or p-VEGFR2 proteins. CONCLUSIONS: Alterations in the structure of the pulmonary circulation in CH piglets by L-citrulline are unlikely to be mediated by overall VEGF signaling. Nonetheless, L-citrulline- induced structural changes should reduce PVR and thereby contribute to the amelioration of CH-induced PH.